AFP-L3 as a Prognostic Predictor of Recurrence in Hepatoblastoma: A Pilot Study. Issue 1 (January 2021) - Kawahara, Insu; Fukuzawa, Hiroaki; Urushihara, Naoto; Kosaka, Yoshiyuki; Kuroda, Yasuhiro; Fujieda, Yuki; Takeuchi, Yuki; Uemura, Kotaro; Iwade, Tamaki; Samejima, Yoshitomo; Morita, Keiichi; Maeda, Kosaku
Abstract : The α-fetoprotein (AFP) level is a sensitive biomarker of active hepatoblastoma (HB). This study aimed to clarify whether the Lens culinaris agglutinin A -reactive fraction of AFP (AFP-L3) after complete resection is a prognostic predictor of HB recurrence. Fourteen HB patients who underwent complete resection of HB were divided into the recurrence group (RG, n=4) and the non-recurrence group (NRG, n=10). The AFP level and AFP-L3 before and after radical surgery were compared between the 2 groups. There was no significant difference in AFP levels in the early postoperative period between the 2 groups ( P =0.54), and AFP was not an early prognostic factor for HB recurrence. At 2 months after surgery, the AFP-L3 fell below the detection limit only in the NRG (7/10 cases) (NRG=70.0% vs. RG=0%, P =0.03). In addition, there were some cases of recurrence in those whose AFP level decreased to the normal range, but none in those whose AFP-L3 fell below the detection limit. In conclusion, the AFP-L3 decreased earlier than did the AFP level; thus, the AFP-L3 after complete resection may be a predictor for HB recurrence.